2014
DOI: 10.1016/j.jneuroim.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Beta-amyloid auto-antibodies are reduced in Alzheimer's disease

Abstract: Accumulation and cytotoxicity of amyloid beta (Aβ) are understood as the major cause of Alzheimer's disease (AD). There is evidence that naturally occurring antibodies against amyloid beta (Aβ) protein play a role in Aβ-clearance, and such a mechanism appears to be impaired in AD. In the present study, the anti-Aβ antibodies in the serum from individuals with and without late onset AD were measured using ELISA and dot-blot methods. Aβ auto-antibodies in serum were mainly targeted to Aβ1-15 epitope and its tite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…The nAbs-Aβ-ELISA showed a high interassay variability. Aggregation of Aβ during the coating process is a possible explanation for this effect [45]. In contrast to our assay design, many ELISAs that investigate nAbs-Aβ antibody titers and that have been reported by others were not controlled for typical quality criteria like unspecific background, interassay variability, or limit of detection and thus their assay performance remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The nAbs-Aβ-ELISA showed a high interassay variability. Aggregation of Aβ during the coating process is a possible explanation for this effect [45]. In contrast to our assay design, many ELISAs that investigate nAbs-Aβ antibody titers and that have been reported by others were not controlled for typical quality criteria like unspecific background, interassay variability, or limit of detection and thus their assay performance remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that different APOE alleles are not associated with an increase in Aβ production, but with an inability to clear Aβ from the brain (Mawuenyega et al, 2010; Castellano et al, 2011). This may be related to the reduced production of Aβ auto-antibodies in AD subjects (Qu et al, 2014). …”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%
“…Previous studies indicated that Aβ species could initiate antibody production in vivo. 7,25 Importantly, microglia activation depends on Aβ conformation and core fragment/epitope of Aβ is related to neuroinflammation. 26 We speculated that editing the hydrophobicity of epitope Aβ17-24 with CRANAD-17 could change immuneresponses of Aβ and consequently alter pro-inflammatory properties of Aβ.…”
Section: Resultsmentioning
confidence: 99%